2019
DOI: 10.1128/jvi.01048-19
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of Heterogeneous Nuclear Ribonucleoprotein (hnRNP) Binding to HIV-1 RNA Reveals a Key Role for hnRNP H1 in Alternative Viral mRNA Splicing

Abstract: Alternative splicing of HIV-1 mRNAs increases viral coding potential and controls the levels and timing of gene expression. HIV-1 splicing is regulated in part by heterogeneous nuclear ribonucleoproteins (hnRNPs) and their viral target sequences, which typically repress splicing when studied outside their native viral context. Here, we determined the location and extent of hnRNP binding to HIV-1 mRNAs and their impact on splicing in a native viral context. Notably, hnRNP A1, hnRNP A2, and hnRNP B1 bound to man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 66 publications
(80 reference statements)
1
24
0
Order By: Relevance
“…HnRNP A1 interacts with the HIV-1 full-length mRNA ( 61–64 ), participating in different stages of its metabolism, including splicing ( 62 , 65 , 66 ), trafficking ( 23 , 67 ), and translation ( 10 , 23 , 36 ). HnRNP A1 interacts with the HIV-1 5′UTR and promotes its IRES activity ( 23 , 64 ).…”
Section: Resultsmentioning
confidence: 99%
“…HnRNP A1 interacts with the HIV-1 full-length mRNA ( 61–64 ), participating in different stages of its metabolism, including splicing ( 62 , 65 , 66 ), trafficking ( 23 , 67 ), and translation ( 10 , 23 , 36 ). HnRNP A1 interacts with the HIV-1 5′UTR and promotes its IRES activity ( 23 , 64 ).…”
Section: Resultsmentioning
confidence: 99%
“…The BCL2L1 pre-mRNA related to greater tumor cell survival in various cancer types, including human lymphoma, breast cancer, prostate cancer and human hepatocellular carcinoma 34 − 35 . AS even found in AIDS, study found AS of HIV-1 mRNAs increases viral coding potential and controls the levels and timing of gene expression 36 . While the role of AS in the thyroid cancer as yet missing, therefore, it was necessary to carry out this study to provide more information about the combination of splicing and clinical parameters, as well as potential mechanism of the survival-related ASEs in TC.…”
Section: Discussionmentioning
confidence: 96%
“…We found that genes harboring retained introns upon filgotinib treatment were enriched in RNA processing and splicing pathways (Supplemental Figure 7, B-H, and Figure 6B). In particular, filgotinib induced intron retention in key RNA processing-related genes in HIV-1 transcription, such as HNRNPH1 (101) and DDX41 (ref. 102 and Figure 6, C-F, blue arrowheads).…”
Section: A Dual-reporter Screen Identified Fda-approved Drugs That Camentioning
confidence: 99%